Homosistein Plasma dan Perubahan Skor Fungsi Kognitif pada Pasien Pasca Stroke Iskemik - Agus Yudawijaya; Endang Kustiowati; Tjokorda Gde Dalem Pemayun (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTPlasma homocysteine and cognitive function score change in post ischemic stroke patients Background: Increase of total homocysteine level is a strong risk factor for cerebrovascular disorder and is correlated with decrease of performance in sort of cognitive tests, including mini mental state examination (MMSE) and clock drawing test (CDT). The aim of this study was to prove the correlation between plasma homocysteine level and change in cognitive function score in postischemic stroke patients. Methods: The design was cross-sectional. The subjects were post-ischemic stroke patients, treated at B1-ward Dr. Kariadi Hospital Semarang from January-June 2010. Plasma homocysteine levels were measured on the first week post onset of ischemic stroke using venous blood at GAKI Laboratory Dr. Kariadi Hospital and cognitive function score was examined using MMSE and CDT on the first and 12th week post onset. Datas were analyzed using descriptive analysis and Spearman’s rho correlation test. Results: Of 30 patients, there were 13 patients with homocysteinemia (43.3%) and 17 with hyperhomocysteinemia (56.7%). There was significant difference of MMSE and CDT score decrease in the first and 12th post onset, with p=0.000 and p=0.001 respectively. Spearman’s rho showed correlation between plasma homocysteine level and cognitive function score based on MMSE with r=-0.837; p=0.000, and based on CDT with r=-0.655; p=0.000. Conclusions: There is strong negative correlation between plasma homocysteine level and change in cognitive function score on the first week post onset of ischemic stroke. Keywords: Homocysteine level, cognitive function score, post-ischemic stroke   ABSTRAK Latar belakang: Peningkatan kadar homosistein plasma merupakan faktor risiko kuat terjadinya penyakit  serebrovaskuler dan dihubungkan dengan penurunan performa sederet tes-tes kognitif, termasuk MMSE (mini mental state examination) dilengkapi oleh CDT (clock drawing test). Tujuan penelitian ini adalah membuktikan hubungan antara homosistein plasma dengan perubahan skor fungsi kognitif pada pasien pasca stroke iskemik. Metode: Desain penelitian adalah cross sectional, pasien pasca stroke iskemik dirawat di Bangsal B1 Saraf RSUP Dr. Kariadi Semarang mulai Januari 2010 sampai Juni 2010. Pemeriksaan homosistein plasma dilakukan pada I minggu pasca onset stroke iskemik menggunakan darah vena di Laboratorium GAKI RSUP Dr. Kariadi dan pemeriksaan skor fungsi kognitif dengan tes MMSE dan CDT dilakukan pada I dan XII minggu pasca onset stroke iskemik. Data di analisis dengan statistik deskriptif dan uji korelasi Spearman’s rho.  Hasil: Didapatkan homosisteinemia pada 13 orang (43,3%) dan hiperhomosisteinemia pada 17 orang (56,7%). Terdapat perbedaan bermakna penurunan skor MMSE dan CDT pada I dan XII minggu pasca onset stroke iskemik dengan nilai p=0,000 dan p=0,001. Uji korelasi Spearman’s rho, menunjukkan koefisien korelasi homosistein plasma dengan skor fungsi kognitif berdasarkan MMSE adalah r=-0,837; p=0,000, sedangkan berdasarkan skor CDT adalah r=-0,655; p=0,000. Simpulan: Didapatkan adanya hubungan kuat dan negatif antara homosistein plasma dengan perubahan skor fungsi kognitif pada I minggu pasca onset stroke iskemik.